2017
DOI: 10.14740/jmc2865w
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic and Severe Infection via Cytomegalovirus and Other Herpesviruses in a Young Apparently Immunocompetent Patient: A Case Report

Abstract: The members of human Herpesviridae family are fully acknowledged as pathogenic agents in immunocompromised individuals, often responsible for a number of severe diseases. On the other hand, in immunocompetent hosts, Herpesviridae-related infections typically display an asymptomatic or paucisymptomatic course, sometimes manifesting with flu-like symptoms. However, such infections can occasionally cause organ damage or multisystemic involvement in healthy subjects. Herein, we describe the first case of a simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…infection of an individual host with multiple HVs has been documented previously [9,[54][55][56]; therefore, it was not surprising to identify multiple HVs within a single host species or individual animal from our sample population, especially given that many of the species had not been previously screened for HVs. Seventeen of the 44 GHVs were identified in more than one species (S2 Table ), with four GHVs observed in host species across both families Cervidae and Bovidae.…”
Section: Plos Onementioning
confidence: 93%
“…infection of an individual host with multiple HVs has been documented previously [9,[54][55][56]; therefore, it was not surprising to identify multiple HVs within a single host species or individual animal from our sample population, especially given that many of the species had not been previously screened for HVs. Seventeen of the 44 GHVs were identified in more than one species (S2 Table ), with four GHVs observed in host species across both families Cervidae and Bovidae.…”
Section: Plos Onementioning
confidence: 93%
“…CMV can cause chronic inflammation of the intestinal mucosa [ 4 ]. Chronic inflammation caused by CMV may inhibit the regeneration of the colonic mucosa, especially in patients with inflammatory bowel disease [ 5 ]. Some studies have suggested that CMV may play a role in the development or progression of UC [ 5 , 6 ]; however, the relationship between the two still needs to be clarified, especially in immunocompetent patients, such as younger patients not taking immunosuppressants.…”
Section: Introductionmentioning
confidence: 99%
“…The self-limiting course of infection typically includes malaise, protracted fever, mild liver-function abnormalities, and lymphocytosis with atypical lymphocytes that occur in ~ 10% of immunocompetent adults [1]. Rarely, immunocompetent patients may develop a severe infection that manifests with multiple organ involvement, co-infection with other viruses could be the explanation for severe and multi-systemic infections [2]. The simultaneous infection by multiple herpesviruses is extremely rare, and because of this, there are limited existing cases published in the literature.…”
Section: Introductionmentioning
confidence: 99%